EFFICIENCY INDICATORS OF COMMERCIAL BANKS IN LIBERALISED ENVIRONMENT IN INDIA - Saurabhi Chaturvedi and Santosh Dhar (Abhigyan, 2009)
Today's environment is dynamic and to succeed organizations must transform to become more responsive, focused, flexible and resilient. Rapid and accurate acquisition of knowledge is essential for organizations to remain viable. Learning for work should be an almost lifelong endeavor, which has a significant influence on an individual and organization. As businesses now have varied locations in different time precinct and employ workers with assorted backgrounds, organizations now seek more inventive and proficient techniques to deliver training to these geographically dispersed workforces. This has fueled the concept of E-Learning. E-Learning is education created and delivered using technologies related to computers, internet and telephony, in combination or in isolation. E-Learning is a major trend and the most rapidly growing method to train people in the organizations. E-Learning permits the delivery of knowledge and information to learners at an accelerated pace, opening up new vistas of knowledge transfer. The acceptability and non-acceptability of a particular technology to a large extent depends on the perception of its users. The paper attempts to identify the difference in perception of males and females, between different age groups and studies whether age and gender interact to affect the perception of E-Learning. This paper is an attempt to understand the finer nuances of implementation of E-Learning in Indian organizations.